Basics of Forming the Indicators of Consolidated Segmental Statements of Integrated Agricultural Enterprises - ALEXANDRA V. Glushchenko; EKATERINA P. Kucherova (Учёт. Анализ. Аудит)
The most important direction of sustainable development of agriculture is agricultural and industrial integration, which can be defined as an economic, informational, organizational and technological association of the enterprises of agriculture with the processing, transportation, servicing and other entities. A complicated multi-level management system, diversified operating activity, wide geography of markets of agricultural produce, regionalization of integrated agricultural enterprises participants call for higher information capacity of accounting and reporting and the formation of discrete and relevant information on the activities of the separate segments of agricultural holdings. Segments of agricultural structures activity often include a lot of interconnected enterprises which are independent legal entities. That is why it is necessary to aggregate the accounting information for the whole group of economic entities forming a segment which is presented as a single economic unit for accounting and reporting purposes. In order to solve this problem the authors developed a method of forming the consolidated information by segments of activity, the special feature of which is a set of procedures involving four interrelated steps: 1) preparatory - defining reporting segments in accordance with the segmentation criteria, working out of uniform accounting policies for segmental reporting purposes, developing indicators and a format of segmented reporting; 2) basic - specification of indicators and formats of worksheets, transformational tables and forms of reporting, collecting the separate statements of the segments, transforming the separate reported information from the analytical forms of the segment participants, followed by elimination of intercompany turnover; 3) consolidating - formation of summary reports and correction tables, consolidated statements, data transfer from the consolidated statements to the forms of segmental reporting; 4) analytical - verification for compliance with the consistency principle and preparing notes to the consolidated segmented information. This method makes it possible to form the aggregated data on financial and economic activities of each segment of an agricultural holding as a single entity in order to search for economic reserves, increase profitability of the business units, assess the level of competitiveness and attractiveness of the segments in the markets and select the optimal range of agricultural products.